The secret of NIMH - Bluth, Don.; Baddeley, Hermione, 1908-1986.; Carradine, John.; DeLuise, Dom.; O'Brien, Robert C.; MGM/UA Home Video (Firm) (Santa Monica, CA : MGM/UA Home Video, 1993)
Mrs. Brisby, a mother mouse, saves her house from the farmer's plow with the help of a crow, an owl and some highly intelligent rats.
Animated.
Based on: Mrs. Brisby and the rats of NIMH / Robert C. O'Brien.
Originally released as a motion picture in 1982.
Music by Jerry Goldsmith ; production executive: Mel Griffin ; directing animators: John Pomeroy, Gary Goldman.
Features voices of Hermione Baddeley, John Carradine, Dom DeLuise, Elizabeth Hartman, Derek Jacobi.
MPAA rating: G.
Keywords: Mice -- Drama; Animated films; Children's films; Video recordings for the hearing impaired; Animal experimentation -- Drama